2016
DOI: 10.11138/ccmbm/2016.13.1.036
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan viscosupplementation: state of the art and insight into the novel cooperative hybrid complexes based on high and low molecular weight HA of potential interest in osteoarthritis treatment

Abstract: SummaryOsteoarthritis (OA) represents a group of chronic, painful, disabling conditions affecting synovial joints. It is characterized by degeneration of articular cartilage, alterations of peri-articular and subchondral bone, low-grade synovial inflammation (synovitis). Despite OA is commonly described as a non-inflammatory disease, it is known that its progression and the subsequent increment of symptoms correlate to the production of inflammatory factors that induce the secretion of enzymes responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The features characterizing the therapeutic course studied herein likely depend on the rational timing of injections with LHA and CLHA, which might exploit and optimize the pharmacokinetic and pharmacodynamics properties of the two forms of HA, in such a way that this regimen results in affordable clinical efficacy and, ultimately, patients' satisfaction. Such an interpretation is in keeping with other and independent evidences indicating that the pharmacodynamic features of HA may profoundly vary as a function of size, structure and chemical modifications (7,9,10,29). These results implicitly suggest that combining different forms of HA such as novel cooperative hybrid complexes or sequential/timed administration of linear and crosslinked preparations as in our case -instead of administering a single, specific form -could recruit multiple and converging mechanisms exalting the pleiotropic nature of native HA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The features characterizing the therapeutic course studied herein likely depend on the rational timing of injections with LHA and CLHA, which might exploit and optimize the pharmacokinetic and pharmacodynamics properties of the two forms of HA, in such a way that this regimen results in affordable clinical efficacy and, ultimately, patients' satisfaction. Such an interpretation is in keeping with other and independent evidences indicating that the pharmacodynamic features of HA may profoundly vary as a function of size, structure and chemical modifications (7,9,10,29). These results implicitly suggest that combining different forms of HA such as novel cooperative hybrid complexes or sequential/timed administration of linear and crosslinked preparations as in our case -instead of administering a single, specific form -could recruit multiple and converging mechanisms exalting the pleiotropic nature of native HA.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the HA fragments, depending on their size, display different rheological properties and have been shown to either stimulate or inhibit inflammatory response in targeted cells and in diseased tissues, and to differently modulate the production of specific inflammatory mediators (5,6). In agreement with the notion of the size-and structure-dependent bioactivity of HA, hybrid preparations of low-and high-MW HA (7,8), crosslinked-HA (9) and hexadecylic-derivatized HA (10) show even further variations/ complexity in terms of pharmacodynamics as compared to the native, linear polymers. From the clinical point of view, according to a Cochrane Database Systematic Review analysis based on a significant number of controlled trials, it has been demonstrated that HA injections significantly reduce pain in knee osteoarthritis (11).…”
mentioning
confidence: 74%
“…Osteoarthritis (OA) is the most commonly occurring degenerative joint disease worldwide [ 1 ]. Affecting primarily middle-aged and older individuals, its incidence has been increasing in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common treatment approaches is viscosupplementation (VS). Balazs and Denlinger [18] introduced this concept, a process in which the pathological SF is replaced by exogenous hyaluronic acid via intra-articular injection, with the hope of restoring the normal viscoelastic properties of SF in the joint and, thus, improving joint mobility [2,[19][20][21]. This approach has recently attracted some controversy regarding its therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%